Suíte para violoncelo solo de Gaspar Cassadó: linguagem nacionalista e a cultura popular espanhola - Guerra, Andrêyna Dinoá Duarte (2011)
The main objective of this research is to formulate interpretative principles and proposals from a comprehensive bibliographic study of folklore and stylistic elements of Spanish music. This research is established from a melodic and structural analysis of the Suite for Solo Cello by Gaspar Cassado, from the performer s perspective, since the work is based on melodies and rhythms of Spain, as well as cultural elements of the Catalonia region. New interpretative challenges are established from the determination of stylistic features of the Suite, considering the composer s origin and his compositional influences.